MEASUREMENT OF GROUND LEVEL OZONE IN SELECTIVE LOCATIONS IN BAGHDAD CITY (Journal of Engineering, 2011)
The ground level ozone concentration at different locations in Baghdad city was identified. Fivedifferent sites have been chosen to identify the ground level ozone concentration. Al- Dora and Al-Za'afarania were chosen as areas contained point source ( power plant station ) in addition to high trafficload , while Al –Uma park, Aden square and Al-Mawal square were chosen as area contained heavytraffic only (line source). The measurement focuses on spring and fall because these periods displayfavorable meteorology to ozone formation. During the research period the maximum values (peaks) forground level ozone concentration were observed at fall: at Al-Za'afarania area 101ppb as an average, atAl-Dora 87 ppb as an average and at line source areas 48 ppb as an average. Among the line sources areaAl-Mawal square represent the highest peak value at fall 68 ppb. At spring the peaks of ozoneconcentration observed to be at the same height, 50 ppb for all sites. The downwind sites from the powerplant stations at Al-Dora and Al-Za'afarania areas record higher ozone peaks compared with up windsites. It can be concluded that the effect of power plant stations in forming ozone is larger than trafficload.The comparison between the ground level ozone concentrations that measured during the research period in spring and fall, and the ambient air quality standards (AAQS) shows that:• No exceeded levels were observed in spring for all sites.• In fall the AAQS for ozone was exceeded in Al-Za'afarania area at 12: PM, 1: PM, 2: PM and 3:PM, and in Al-Dora at 2: PM.